Urogenital anomalies associated with anorectal malformation - Srivastava Vaishali; Ray A; Patra R; Saha Basu K; Samanta N; Saha K (Wolters Kluwer Medknow Publications, 2005)
Background: The objective of the paper is to review the incidence and types of associated urogenital anomalies (U.G.A.) we encountered in patients with anorectal malformations (A.R.M.) and compare the results with previously published world literature. Materials and Methods: Retrospective review was done of 220 cases of A.R.M., treated from May 2002 to April 2003. All patients routinely underwent ultrasound (U.S.) study of the K.U.B. region and pelvis and lumbosacral radiography. Voiding cystourethrography (V.C.U.G.), nuclear renography and other investigations like buccal smear and karyotyping were done in selected cases only. Results: Genital anomalies were found in 30 cases (13.63%) and urologic anomalies in 25 cases (11.36%), a direct correlation being found between the level of A.R.M. and the incidence of urogenital anomalies (U.G.A.). Conclusion: The high incidence of associated anomalies (24.54%) makes careful clinical examination and evaluation of the urinary tract during the neonatal or early infantile period mandatory in all cases of A.R.M., particularly to avoid deterioration of renal function in future.